2012
DOI: 10.3399/bjgp12x649133
|View full text |Cite
|
Sign up to set email alerts
|

Reassured or fobbed off? Perspectives on infertility consultations in primary care: a qualitative study

Abstract: BackgroundInfertility affects 9% of couples in the UK. Most couples who visit their GP because they are worried about their fertility will ultimately conceive, but a few will not. Treatment usually happens in secondary care, but GPs can have an invaluable role in starting investigations, referring, and giving support throughout treatment and beyond. AimTo inform clinical practice by exploring primary care experiences of infertility treatment among females and males, and discussing findings with a reference gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
(22 reference statements)
0
22
0
Order By: Relevance
“…) so that the protocol could be personalised, a relaxing atmosphere could be created and patients could be made to feel that they are being thoroughly respected (Hinton et al . ). Consequently, nurses may be in a privileged position to perform this procedure as some studies have shown that they are capable of carrying out the examination with satisfactory results on a clinical and emotional level (Williams et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) so that the protocol could be personalised, a relaxing atmosphere could be created and patients could be made to feel that they are being thoroughly respected (Hinton et al . ). Consequently, nurses may be in a privileged position to perform this procedure as some studies have shown that they are capable of carrying out the examination with satisfactory results on a clinical and emotional level (Williams et al .…”
Section: Discussionmentioning
confidence: 97%
“…In this context, care based on the human care theory is believed to reduce the negative impact of infertility on women undergoing treatment and increase self-efficacy and adjustment (Arslan-€ O zkan et al 2014). Therefore, as previously suggested by other authors, professionals with a more long-standing relationship with the couple should access hysterosalpingography (Wilkes et al 2009) so that the protocol could be personalised, a relaxing atmosphere could be created and patients could be made to feel that they are being thoroughly respected (Hinton et al 2012). Consequently, nurses may be in a privileged position to perform this procedure as some studies have shown that they are capable of carrying out the examination with satisfactory results on a clinical and emotional level (Williams et al 2010).Nonetheless and regardless of who performs the procedure, patient-centred care could increase users' satisfaction (Dancet et al 2012, Cunningham & Cunningham 2013 and this should be considered the cornerstone when designing and providing services to people involved in the infertility process.…”
Section: Discussionmentioning
confidence: 99%
“…23 There may be some discrepancy between patients’ and providers’ perceptions of what constitutes seeking infertility care, and this may contribute to some patients feeling as though their fertility concerns are not taken seriously by generalist providers. 24 Despite its high prevalence, infertility may be an infrequently addressed topic in family medicine residencies and other primary care training programs.…”
Section: Discussionmentioning
confidence: 99%
“…Participants' previous experience of infertility treatment also appeared to deter them from preparing for the birth and parenthood, and disclosing negative feelings to others about the pregnancy. This is important as research that has explored the experiences of antenatal care in the normal birth population suggests that, although couples value a strong relationship with their GP where concern and interest is shown in their physical and mental health, 24,25 they commonly complain of feeling unable to communicate with their GP or midwife [26][27][28][29] and often feel their GP has little knowledge, or interest, in antenatal care services. 27 Current guidelines from the National Institute for Health and Care Excellence for the delivery of antenatal and postnatal care give no consideration to the specific needs of couples who have conceived through fertility treatment.…”
Section: Resultsmentioning
confidence: 99%